Use of a nickel-based metal organic framework (Ni-MOF) material
Patent Information
- Application Number
- CN202311262810.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-09-27
AI Technical Summary
目前关于活性炭、离子交换树脂和氧化铝吸附F-53B的研究报道较多,其虽然也能吸附水中的F-53B,但在实际应用过程中还存在运行成本较高和易受阴离子影响等问题
[0023]本发明的镍基金属有机骨架材料的应用具有如下优势:
Smart Images

Figure CN118236978B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water pollution purification, specifically to the application of a nickel-based metal-organic framework (Ni-MOFs) material. Background Technology
[0002] Metal-organic frameworks (MOFs) are a class of compounds that form one-dimensional, two-dimensional, or three-dimensional structures by coordination of metal ions or metal clusters with organic ligands. MOF materials can be used for storage, separation, and catalysis.
[0003] Existing patent 202210923022.X discloses a two-dimensional nickel-based metal-organic framework catalyst, its preparation method, and its application. This MOF material can achieve efficient one-step synthesis of styrene cyclic carbonates from styrene and CO2 under mild conditions. The patent discloses the following steps: Ni(CH3COO)2·4H2O is dissolved in 60 mL of deionized water and sonicated to obtain a green transparent solution A; 0.0831 g of 1,4-H2BDC is dissolved in 60 mL of DMAC and sonicated to obtain solution B; solution A is poured into solution B to obtain a mixed solution C; mixed solution C is refluxed at 130 °C for 3 h and then filtered; the obtained product is washed with deionized water and methanol, purified with methanol for 24 h, filtered, and then vacuum dried at 60 °C for 10 h to obtain the two-dimensional nickel-based metal-organic framework catalyst.
[0004] Perfluorooctane sulfonate (PFOS) has numerous C-F bonds, exhibiting high polarity and stability. Due to the presence of hydrophilic sulfonic acid groups (-SO3H) at its chain ends, it is partially soluble in water. PFOS possesses low surface tension and excellent chemical stability, and is commonly used as a chromium mist suppressant in hard chromium plating. However, PFOS is persistent, bioaccumulative, and biomagnifying, and can trigger various toxic effects. Therefore, PFOS is classified as a persistent organic pollutant (POPs), with detectable concentrations in environmental water bodies reaching 10–50 ng / L. -1 Perfluoroalkyl ether sulfonates (F-53B) are a substitute for PFOS and have been used in the Chinese electroplating industry for over 30 years without any regulation. This has resulted in large amounts of F-53B being released into natural water bodies, with detection levels approaching those of PFOS, reaching 10–50 ng / L. -1Although the concentration of F-53B detected in natural water bodies is low, its environmental persistence and bioaccumulation mean that even low concentrations may pose significant health risks. Studies have shown that the toxicity of F-53B is equivalent to or even higher than PFOS. Research by Zhao Nan et al. also indicates that exposure to F-53B in rats may affect serum oxidative stress, inducing inflammation, cardiovascular disease, diabetes, and hypertension, as well as neurotoxicity and inhibiting brain development. Therefore, eliminating F-53B pollution of the aquatic environment is imperative.
[0005] The main technologies for removing F-53B from water include adsorption, electrochemical oxidation, photodegradation, and mechanochemical degradation. Due to the high stability of F-53B, electrochemical oxidation, photodegradation, and mechanochemical degradation have low defluorination rates and cannot completely degrade F-53B. Adsorption is considered one of the most effective strategies for removing F-53B from water. Currently, there are many research reports on the adsorption of F-53B by activated carbon, ion exchange resins, and alumina. Although they can adsorb F-53B from water, their practical applications still suffer from high operating costs and susceptibility to anion interference. Summary of the Invention
[0006] In response to the above problems, the inventors of this application discovered during their catalytic research on nickel-based metal-organic frameworks that nickel-based metal-organic frameworks can not only be used as catalysts, but also achieve ultra-high efficiency adsorption of F-53B.
[0007] Currently, the available materials for adsorbing F-53B are very limited, and most are severely affected by anions during the adsorption process. The inventors of this application have significantly reduced the influence of anions on their nickel-based metal-organic framework, and through ion exchange, the influence of anions can be made negligible.
[0008] To address this problem, the present invention provides an application of a nickel-based metal-organic framework (Ni-MOFs) material, characterized in that the Ni-MOFs material is used to adsorb F-53B.
[0009] In a preferred embodiment, the two-dimensional Ni-MOFs material is used to treat contaminated water or electroplating wastewater containing F-53B.
[0010] In a preferred embodiment, the application includes adding calcium chloride to polluted water or electroplating waste liquid, using the chloride ions therein to replace phosphate ions, and depositing and filtering the resulting insoluble calcium salt, and then adding Ni-MOFs material to the polluted water or electroplating waste liquid.
[0011] In a preferred embodiment, the preparation steps of the nickel-based metal-organic framework (Ni-MOFs) material are as follows:
[0012] (1) Dissolve the first dose of nickel acetate tetrahydrate Ni(OAc)2·4H2O in deionized water;
[0013] (2) Dissolve the second dose of terephthalic acid BDC in N,N-dimethylacetamide DMA;
[0014] (3) Mix the two solutions prepared in step (1) and step (2) and reflux and stir them in a certain temperature environment;
[0015] (4) The solution obtained in step (3) is filtered, washed and vacuum dried to finally obtain Ni-MOFs.
[0016] In a preferred embodiment, after step 3, the solution is further further comprising: cooling the solution to 80°C; dissolving 1 mol caprolactam and 1.5 mol sodium hydroxide in 500 g of deionized water, heating to 100°C, stirring for 1 h, cooling, and neutralizing with dilute sulfuric acid to pH 7.5. The neutralized solution is then desalted; the desalted substance is decolorized, filtered, and concentrated at low temperature. Simultaneously, methanol or ethanol solution is added, and the mixture is stirred to crystallize, yielding 6-aminohexanoic acid. 1 mmol of 6-aminohexanoic acid is dissolved in deionized water, and 0.5 mmol of calcium hydroxide is added to the solution. The mixture is heated to 80°C, and the resulting solution is added to the solution obtained in step 3, and stirred for 1 h.
[0017] Two-dimensional grafted Ni-MOFs were obtained by filtration, washing, and vacuum drying.
[0018] In a preferred embodiment, the molar ratio of the first dose to the second dose is 12:5.
[0019] In a preferred embodiment, the first dose is 1.2 mmol and the deionized water is 50-80 mL.
[0020] In a preferred embodiment, the second dose is 0.5 mmol, and the N,N-dimethylacetamide (DMA) is 50-80 mL.
[0021] In a preferred implementation, the specific temperature environment is 150-180℃.
[0022] Technical effect
[0023] The application of the nickel-based metal-organic framework material of the present invention has the following advantages:
[0024] 1. The two-dimensional Ni-MOFs material of the present invention exhibits good applicability to complex actual aquatic environments and high anti-interference ability when used for the adsorption of perfluoroalkyl ether sulfonates, even when a large amount of CO3 is present in the water. 2- SO4 2- NO3 - or Cl - Adsorption remains unaffected even when PO4 is present in the water, thanks to pretreatment or grafting of the adsorbent material. 3- At the same time, it can also achieve good anti-interference performance and can efficiently and quickly adsorb fluorine-containing compounds such as F-53B;
[0025] 2. The method of the present invention has a short preparation time and simple operation, and the use of Ni as the metal center of MOFs material has the advantages of low price and high reactivity. Attached Figure Description
[0026] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings:
[0027] Figure 1 The adsorption isotherm of F-53B on Ni-MOFs material;
[0028] Figure 2 SEM images of sample 1 (left) and sample 2 (right);
[0029] Figure 3 The pore size distribution diagrams are for samples 1 and 2.
[0030] Figure 4 The XRD and FTIR spectra of samples 1 and 2 before and after adsorption of F-53B are shown.
[0031] Figure 5 The graphs show the weight loss curves and weight loss rate curves for samples 1 and 2.
[0032] Figure 6 The fitting curves for the adsorption kinetics, pseudo-first-order kinetics, and pseudo-second-order kinetics models of F-53B for samples 1 and 2 are shown.
[0033] Figure 7 Fitting curves for Langmuir and Freundlich adsorption isotherms of samples 1 and 2;
[0034] Figure 8 The effect of coexisting anions on the adsorption of F-53B in two-dimensional Ni-MOFs materials;
[0035] Figure 9 The adsorption energy distribution of F-53B molecules on sample 1 and sample 2 is shown.
[0036] Figure 10The graphs show the weight loss curve and weight loss rate curve for sample 5.
[0037] Figure 11 The effect of coexisting anions on the adsorption of F-53B on two-dimensional grafted Ni-MOFs materials. Detailed Implementation
[0038] Through extensive experimental research, the inventors of this application discovered that two-dimensional Ni-MOFs have excellent adsorption performance and anti-interference ability.
[0039] Example 1
[0040] The preparation process of the two-dimensional Ni-MOFs material in this embodiment is as follows:
[0041] 1. Dissolve 1.2 mmol of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 60 mL of deionized water;
[0042] 2. Dissolve 0.5 mmol of terephthalic acid (BDC) in 60 mL of N,N-dimethylacetamide (DMA);
[0043] 3. Mix the two solutions from steps 1 and 2, and stir under reflux at 150°C for 3 hours;
[0044] 4. The solution in step 3 was filtered, washed, and vacuum dried to obtain sample 1, denoted as two-dimensional Ni-MOFs.
[0045] Comparative Example 1
[0046] The preparation process is as follows:
[0047] 1. Dissolve 1.2 mmol of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 60 mL of deionized water;
[0048] 2. Dissolve 0.5 mmol of terephthalic acid (BDC) in 60 mL of N,N-dimethylacetamide (DMA);
[0049] 3. Mix the two solutions from steps 1 and 2, and stir under reflux at 100°C for 3 hours;
[0050] 4. The solution in step 3 was filtered, washed, and vacuum dried to obtain sample 2, which was denoted as three-dimensional Ni-MOFs.
[0051] Comparative Example 2
[0052] The preparation process is as follows:
[0053] 1. Dissolve 1.2 mmol of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 60 mL of deionized water;
[0054] 2. Dissolve 0.5 mmol of terephthalic acid (BDC) in 60 mL of N,N-dimethylacetamide (DMA);
[0055] 3. Mix the two solutions from steps 1 and 2, and stir under reflux at 120°C for 3 hours;
[0056] 4. Filter, wash and vacuum dry the solution in step 3 to obtain sample 3.
[0057] Example 2
[0058] The preparation process is as follows:
[0059] 1. Dissolve 1.2 mmol of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 60 mL of deionized water;
[0060] 2. Dissolve 0.5 mmol of terephthalic acid (BDC) in 60 mL of N,N-dimethylacetamide (DMA);
[0061] 3. Mix the two solutions from steps 1 and 2, and stir under reflux at 160°C for 3 hours;
[0062] 4. Filter, wash, and vacuum dry the solution from step 3 to obtain sample 4.
[0063] Observations of the samples in Comparative Example 1, Comparative Example 2, and Examples 1 and 2 revealed that Comparative Example 1 primarily contained three-dimensional Ni-MOF materials, while Comparative Example 2 contained some two-dimensional materials. The materials in Example 1 contained only a small amount of three-dimensional materials, while the samples in Example 2 were almost entirely two-dimensional materials. Therefore, in this application, the preparation temperature is set at 140 or 150 degrees Celsius or higher, more preferably 155 degrees Celsius or higher up to 180 degrees Celsius.
[0064] Performance and morphology testing
[0065] The following describes in detail the morphology and performance testing process using Sample 1 and Sample 2 as examples. First, adsorption isotherm measurements were performed on Sample 1 obtained in Example 1 and Sample 2 obtained in Comparative Example 1. Figure 1 As shown, Sample 1 exhibits a higher adsorption capacity for F-53B. This was achieved when the initial F-53B concentration was 150 mg·L⁻¹. -1 At that time, the adsorption capacity of sample 1 reached 451.2 mg·g. -1 The value was significantly higher than that of other samples.
[0066] Further testing was conducted on samples 1 and 2, and the morphological and performance test results are as follows:
[0067] (I) Microstructure Characterization
[0068] like Figure 2As shown in the SEM images, Sample 2 exhibits a distinct blocky morphology, classifying it as a three-dimensional material, while Sample 1 displays a well-dispersed lamellar structure, classifying it as a two-dimensional material. This lamellar structure fully exposes the active sites, resulting in excellent adsorption performance in the F-53B adsorption test. Furthermore, the lateral dimensions of the microplates in Sample 1 are significantly larger than their thickness, leading to a curved or coiled morphology. This curvature or twisting forms a distinct mesoporous structure.
[0069] Figure 3 The pore size distribution characteristics confirm that these curved microplate structures provide sufficient channels for mass transfer of guest molecules.
[0070] The specific surface area of sample 1 reached 58.4 m². 2 ·g -1 The specific surface area of sample 1 is significantly higher than that of sample 2 (21.1 m²). 2 ·g -1 This shows that two-dimensional Ni-MOFs can provide more adsorption sites than three-dimensional Ni-MOFs, which is beneficial to the adsorption of F-53B.
[0071] From XRD patterns ( Figure 4 (a) As can be seen, the two-dimensional Ni-MOFs corresponding to sample 1 still have obvious characteristic peaks after adsorbing F-53B, indicating that the two-dimensional Ni-MOFs have good stability and still have good crystal structure after adsorbing F-53B; while the three-dimensional Ni-MOFs corresponding to sample 2 have some characteristic peaks disappear after adsorbing F-53B, indicating that the stability of the three-dimensional Ni-MOFs is weak and the structure may have collapsed after adsorbing F-53B.
[0072] From FTIR spectra ( Figure 4 (b) shows that after the two Ni-MOFs materials adsorbed F-53B, the original location at 466 cm⁻¹ was... -1 and 525cm -1 The Ni-O stretching vibration peaks shifted to 460 cm⁻¹. -1 and 520cm -1 This is likely due to the electrostatic interaction between F-53B and the two Ni-MOF materials, indicating that electrostatic interaction is one of the important mechanisms by which the two Ni-MOF materials adsorb F-53B.
[0073] (II) Thermal stability testing
[0074] like Figure 5As shown, the mass loss of the samples within the range of 40–800℃ mainly occurs in two stages. The first stage of weight loss occurs between 100 and 250℃, which is due to the release of water molecules (mainly free water and water of crystallization) from the pores in the material. The second stage of weight loss begins around 400℃, at which point the weight loss curve shows a sharp downward trend, indicating that the metal-organic framework of the material begins to collapse and the material begins thermal decomposition, with the mass loss exceeding 60% in this stage. The DTG curves further confirm this, showing a significant response in the range of 380–490℃, and the response temperature of the two-dimensional Ni-MOFs (sample 1) (468℃) is slightly higher than that of the three-dimensional Ni-MOFs (sample 2) (456℃). Therefore, it can be concluded that the two Ni-MOF materials have good overall thermal stability, and the two-dimensional Ni-MOFs exhibit better thermal stability than the three-dimensional Ni-MOFs.
[0075] (III) Adsorption characteristics of Ni-MOFs for F-53B
[0076] The morphology and performance of the treated water were tested using Sample 1 and Sample 2, respectively.
[0077] 1) Adsorption kinetics fitting and analysis: The kinetic fitting results of Ni-MOFs adsorption of F-53B are as follows: Figure 6 As shown in (a), the entire adsorption process can be roughly divided into three stages: rapid adsorption, slow adsorption, and equilibrium. For the three-dimensional Ni-MOFs material (sample 2), the rapid adsorption stage occurs from 0 to 4 min. During this stage, the MOFs material surface has abundant adsorption active sites, which can provide a large number of bonding sites, thereby promoting the adsorption of F-53B, resulting in a high adsorption rate. Subsequently, the adsorption rate is slower from 4 to 12 min. This is because F-53B occupies a large number of adsorption sites, increasing the concentration of guest molecules on the adsorbent surface, leading to a decrease in the concentration difference between the solution and the adsorbent surface, and a decrease in the mass transfer driving force, thus slowing down the increase in adsorption capacity. As the adsorption time increases (after more than 12 min), the adsorption basically reaches stability, and the adsorption reaches equilibrium with an equilibrium capacity of 195.6 mg·g⁻¹. -1 In contrast, two-dimensional Ni-MOFs (sample 1) rapidly adsorbed F-53B within 0–2 min, with a significantly higher adsorption rate than three-dimensional Ni-MOFs. This is because the two-dimensional structure exposes more active adsorption sites than the corresponding three-dimensional structure. Figure 2 The adsorption rate of F-53B is significantly enhanced due to the confinement effect. Furthermore, the adsorption rate of this material is faster than that of most adsorbents reported in the literature, and the two-dimensional Ni-MOFs approach adsorption equilibrium within 2 minutes, with an equilibrium adsorption capacity of 224.6 mg·g⁻¹. -1It is higher than the equilibrium capacity of three-dimensional Ni-MOFs (195.6 mg·g⁻¹). -1 This demonstrates that the change in microstructure transforms three-dimensional MOFs into two-dimensional MOFs, greatly improving the efficient and rapid adsorption of F-53B.
[0078] right Figure 6 The results in (a) were fitted using pseudo-first-order and pseudo-second-order dynamics, and the results are as follows: Figure 6 (b) Figure 6 As shown in (c). Compared with the pseudo-first-order kinetic model, the pseudo-second-order kinetic model has better correlation (R2 = 0.9999), and the qecal value calculated by the model is closer to the actual measured value. This indicates that the pseudo-second-order kinetic model can describe the adsorption process more accurately, and further shows that the adsorption process of Ni-MOFs on F-53B involves chemisorption.
[0079] 2) Fitting adsorption isotherm data: The fitting results of the Langmuir and Freundlich models to the isotherm data are as follows: Figure 7 (a) and Figure 7 As shown in (b), the Freundlich model (R² > 0.98) more accurately describes the adsorption process of F-53B on the two Ni-MOF materials. These results indicate that the adsorption of F-53B on the surfaces of the two Ni-MOF materials is not a simple monolayer adsorption, but rather a heterogeneous multilayer adsorption. This may be because the hydrophobic functional group C–F in F-53B generates hydrophobic aggregation.
[0080] 4) Adsorption mechanism of Ni-MOFs for F-53B in water
[0081] Depend on Figure 9 As can be seen from the adsorption energy curves, the adsorption energies of the two Ni-MOF materials are relatively small (below 83.68 kJ / mol). -1 This indicates that the adsorption of F-53B by these two materials is mainly physical adsorption (including electrostatic interactions and van der Waals forces), followed by chemical adsorption (direct bonding to form complexes). Furthermore, the adsorption capacity of three-dimensional Ni-MOFs for F-53B is slightly higher than that of two-dimensional Ni-MOFs. Although three-dimensional Ni-MOFs exhibit a stronger adsorption force for F-53B, the homogeneity of their surface and their bulk morphology limit the number of active adsorption sites. The lack of confinement between different layers further reduces the free diffusion coefficient of F-53B in three-dimensional Ni-MOFs (6.86 × 10⁻⁶). -9 cm 2 ·s -1 The free diffusion coefficient is significantly higher than that in two-dimensional Ni-MOFs (1.18 × 10⁻⁶).-10 cm 2 ·s -1 This makes it difficult for F-53B to be stably adsorbed on the surface of three-dimensional Ni-MOFs, which is also the main reason why the equilibrium adsorption constant of two-dimensional Ni-MOFs is greater than that of three-dimensional Ni-MOFs.
[0082] Environmental adaptability characterization
[0083] The adsorption process of perfluoroalkyl ether sulfonates using various samples is as follows:
[0084] The water to be treated (taking the effluent after secondary physicochemical treatment of chromium plating wastewater as an example) is subjected to sedimentation treatment for 4-8 hours;
[0085] After sedimentation, the supernatant was collected and filtered.
[0086] Adding Ni-MOFs material: For general chromium plating wastewater after secondary physicochemical treatment, the dosage of Ni-MOFs material is 0.1-5 g / L. Stirring or aeration is used to uniformly disperse the Ni-MOFs material in the aqueous solution.
[0087] To verify its environmental adaptability, CO3 was added to the test water. 2- SO4 2- NO3 - or Cl - PO4 3- Interfering ions.
[0088] like Figure 8 As shown, the adsorption percentage of F-53B by two-dimensional Ni-MOFs (sample 1) is affected by CO3. 2- SO4 2- NO3 - or Cl - The impact is very small, almost negligible, demonstrating excellent anti-interference ability, while coexisting with PO4 3- However, the adsorption percentage dropped significantly to around 80%. Since phosphate is a common anion in wastewater, it is necessary to reduce its impact on adsorption.
[0089] To address the aforementioned problems, the inventors of this application conducted further research and obtained two solutions:
[0090] Option 1
[0091] Considering PO4 3- To mitigate the impact of phosphate ions on adsorption and further enhance adsorption capacity, ion substitution is performed during the pretreatment stage of adsorption testing by adding calcium chloride to replace phosphate ions with Cl-. - This further improves the adsorption efficiency.
[0092] Specifically, the improved processing solution is as follows:
[0093] The water to be treated (taking the effluent after secondary physicochemical treatment of chromium plating wastewater as an example) is subjected to sedimentation treatment for 4-8 hours;
[0094] After sedimentation, the supernatant was collected and filtered.
[0095] Take a small amount of filtered water sample and determine the phosphate content (PO4) in the water. 3- Whether the content exceeds the standard (e.g., whether it exceeds 10 mmol / L);
[0096] If the content exceeds the standard, add calcium chloride or calcium nitrate to the water to be treated, stir, and filter again after calcium phosphate or calcium carbonate has settled.
[0097] Ni-MOFs material was added to the water to be treated after secondary filtration for adsorption treatment. For the tailwater after secondary physicochemical treatment of general chromium plating wastewater, the dosage of Ni-MOFs material was 0.1 g / L. The Ni-MOFs material was uniformly dispersed in the aqueous solution by stirring or aeration.
[0098] Due to PO4 in the pretreatment 3- Most of it is replaced by deposition, so this method can achieve the desired effect for PO4. 3- Improved anti-interference capability.
[0099] Option 2
[0100] While Scheme 1 can reduce the impact of phosphate on the adsorption process, it increases the testing and filtration processes, making the procedure more cumbersome. Furthermore, calcium phosphate is not completely insoluble in water and cannot be completely deposited through salt formation. Therefore, this scheme is proposed.
[0101] This scheme adjusts the preparation method to enhance the anti-interference ability of Ni-MOFs materials against anions, especially phosphate ions.
[0102] 1. Dissolve 1.2 mmol of nickel acetate tetrahydrate (Ni(OAc)2·4H2O) in 60 mL of deionized water;
[0103] 2. Dissolve 0.5 mmol of terephthalic acid (BDC) in 60 mL of N,N-dimethylacetamide (DMA);
[0104] 3. Mix the two solutions from steps 1 and 2, stir under reflux at 150°C for 3 hours, and then cool the mixture to 80°C;
[0105] 4. Dissolve 1 mol caprolactam and 1.5 mol sodium hydroxide in 500 g of deionized water, heat to 100 °C, stir for 1 h, cool, and neutralize with dilute sulfuric acid to pH 7.5. Desalt the neutralized solution; decolorize the desalted substance, filter (this process can be repeated multiple times), and concentrate at low temperature. Simultaneously, add methanol or ethanol solution, stir to crystallize, and obtain 6-aminohexanoic acid. Dissolve 1 mmol of 6-aminohexanoic acid in deionized water, add calcium hydroxide to the solution, and heat to 80 °C.
[0106] 5. Add the solution obtained in step 4 to the solution obtained in step 3, and stir for 1 hour.
[0107] After filtration, washing, and vacuum drying, sample 5 was obtained, denoted as two-dimensional grafted Ni-MOFs.
[0108] Thermal stability testing was performed on sample 5.
[0109] like Figure 10 As shown, due to the grafting of calcium 6-aminohexanoate, the thermal stability of sample 5 decreased. However, considering that sample 5 is mainly used for adsorption rather than as a catalyst, this decrease in thermal stability does not significantly affect its adsorption performance. Similar to other samples, the first stage of weight loss in sample 5 occurs between 100 and 250 °C, which is due to water molecules in the material. The second stage of weight loss begins at approximately 380 °C, at which point the weight loss curve shows a sharp downward trend, indicating that the metal-organic framework of the material begins to collapse and calcium 6-aminohexanoate begins to thermally decompose, with a mass loss exceeding 65% in this stage.
[0110] The adsorption adaptability test was performed on sample 5, and the results are as follows: Figure 11 As shown in the figure, the adsorption percentage of various anions by both methods is affected by CO3. 2- SO4 2- NO3 - Cl - PO4 3- The effects of PO4 are very small, demonstrating excellent anti-interference properties. This may be because 6-aminohexanoic acid has a relatively long chain structure, with the amino side more tightly connected to the metal framework, while the carboxyl side extends outward and releases calcium ions during adsorption to bind with phosphate, reducing the influence of phosphate. Experimental results show that two-dimensional grafted Ni-MOFs can exhibit better adsorption capacity for F-53B in complex real-world aquatic environments, reducing the influence of PO4. 3- The impact.
[0111] In summary, the inventors of this application have found an adsorbent material capable of effectively adsorbing F-53B, possessing adaptability to complex real-world aquatic environments, and exhibiting high resistance to interference, especially when a large amount of CO3 is present in the water. 2- SO4 2- NO3 - or Cl - Adsorption is unaffected when PO4 is present in water, and through pretreatment or grafting with 6-aminohexanoic acid, the adsorption is also unaffected. 3- At the same time, it can also achieve good anti-interference performance and can efficiently and quickly adsorb fluorine-containing compounds such as F-53B; the present invention uses Ni as the metal center of MOFs material, which has the advantages of low price and high reactivity.
[0112] Although the principles of the present invention have been described in detail above in conjunction with preferred embodiments, those skilled in the art should understand that the details in the embodiments do not constitute a limitation on the scope of the present invention. Any obvious changes, such as equivalent transformations or simple substitutions based on the technical solutions of the present invention, without departing from the spirit and scope of the present invention, fall within the protection scope of the present invention.
Claims
1. An application of a nickel-based metal-organic framework (Ni-MOFs) material, characterized in that, The nickel-based metal-organic framework (Ni-MOFs) material is used to adsorb F-53B. The preparation steps of the nickel-based metal-organic framework (Ni-MOFs) material are as follows: (1) Dissolve the first dose of nickel acetate tetrahydrate Ni(OAc)2·4H2O in deionized water, where the first dose is 1.2 mmol and the deionized water is 50-80 mL; (2) Dissolve the second dose of terephthalic acid in N,N-dimethylacetamide, wherein the second dose is 0.5 mmol and the N,N-dimethylacetamide is 60 mL; (3) Mix the two solutions prepared in step (1) and step (2) and reflux and stir them in a certain temperature environment, wherein the certain temperature is 160℃; (4) Cool the solution obtained in step (3) to 80°C; dissolve 1 mol caprolactam and 1.5 mol sodium hydroxide in 500 g deionized water, heat to 100°C, stir for 1 h, cool, neutralize with dilute sulfuric acid to pH=7.5, and desalt the neutralized solution; decolorize the desalted substance, filter, and concentrate at low temperature, while adding methanol or ethanol solution, stirring to crystallize, to obtain 6-aminohexanoic acid, take 1 mmol of 6-aminohexanoic acid and dissolve it in deionized water, add 0.5 mmol of calcium hydroxide to the solution, heat to 80°C, add the obtained solution to the solution obtained in step (3), stir for 1 h, filter, wash and vacuum dry to obtain two-dimensional grafted nickel-based metal-organic framework Ni-MOFs material.
2. The application according to claim 1, characterized in that, The two-dimensional grafted nickel-based metal-organic framework (Ni-MOFs) material is used to treat polluted water containing F-53B.
3. The application according to claim 2, characterized in that, The application involves adding calcium chloride to polluted water containing F-53B, using the chloride ions to replace phosphate ions, and then depositing and filtering the resulting insoluble calcium salt, followed by adding two-dimensional grafted nickel-based metal-organic framework (Ni-MOF) materials to the polluted water.
Citation Information
Patent Citations
A two-dimensional nickel-based metal-organic framework catalyst, its preparation method and application
CN115400796B
Preparation method for organic-inorganic composite modified straw phosphorus-removing adsorbing material
CN108262029A